A Comparative Study of Ripasa Score and Alvarado Score in Diagnosis of Acute Appendicitis - Muhammad, Jan; Asad, Muhammad; Farhan, Muhammad; Shah, Abdullah; Kakakhel, Siraj Muneer; Mehroz, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Among the most frequent causes of right iliac fossa pain is acute appendicitis. Developed to lower the likelihood of negative appendectomy are several scoring systems for diagnosing acute appendicitis. Objective: This study was motivated by a comparison of the RIPSA score with the Alvarado score based on histology reports for the diagnosis of acute appendicitis. Methods: Between November 2023 and June 2024, the emergency general surgery department at Lady Reading Hospital, Peshawar, conducted a prospective cross-sectional study. Based on histopathology data, both scoring methods were applied to the same patient and assessed for sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy. Alvarado achieved a score of 7.5, which coincided with RIPASA’s cut-off value of 7.5.Results: The study included a total of 194 patients. With values of 97.42% and 86.08%, respectively, the RIPASA score demonstrates a higher diagnostic accuracy than the Alvarado score. For RIPASA, sensitivity, specificity, PPV, and NPV came at 98.86%, 84.21%, 98.3%, and 88.89%, respectively. By contrast, Alvarado had sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of 96.89%, 33.33%, 87.64%, and 68.75%, respectively. Conclusion: Then the RIPASA scoring system shows better sensitivity, specificity, and diagnostic accuracy than the Alvarado scoring system.